1998
DOI: 10.1016/s0735-1097(98)00337-4
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular ejection fraction is an independent predictor of survival in patients with moderate heart failure

Abstract: In addition to the NYHA classification and to the percent of maximal predicted VO2, RVEF is an independent predictor of survival in patients with moderate CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
277
1
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 589 publications
(300 citation statements)
references
References 25 publications
14
277
1
8
Order By: Relevance
“…In humans, right heart assessment has been shown to have a clinically relevant impact on predicting clinical status and outcome in a variety of cardiovascular diseases, including diseases conventionally viewed as left heart‐specific, such as mitral valve disease and HCM 12, 23, 24, 25, 26. Recently, RV function has also been shown to have prognostic value in dogs with arrhythmogenic RV cardiomyopathy and myxomatous mitral valve disease 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, right heart assessment has been shown to have a clinically relevant impact on predicting clinical status and outcome in a variety of cardiovascular diseases, including diseases conventionally viewed as left heart‐specific, such as mitral valve disease and HCM 12, 23, 24, 25, 26. Recently, RV function has also been shown to have prognostic value in dogs with arrhythmogenic RV cardiomyopathy and myxomatous mitral valve disease 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Although the decrease in systemic vascular resistance may have played a role, the increase in cardiac index also serves to emphasize the importance of right ventricular unloading in heart failure patients and its potential favourable impact on diastolic ventricular interaction [12]. The relevance of this response is evident by the prognostic significance of right ventricular ejection fraction in heart failure patients [13]. This increase in cardiac index could be a marker of better short term prognosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…32 In patients with advanced HF-rEF, studies have shown that right ventricular (RV) function predicts survival. [33][34][35] Until recently there were few data published on RV function and survival in HFpEF, but Melenovsky et al 36 recently showed that RV dysfunction was present in a third of patients with HF-pEF. Those with RV dysfunction and HF-pEF had worse hemodynamics at RHC, and RV dysfunction was a strong predictor of mortality.…”
Section: Clinical Implications Of Ph In Hf-pefmentioning
confidence: 99%